Prediksi Jumlah Pendapatan Beasiswa PPA dan BBP Menggunakan Jaringan Syaraf Tiruan Backpropagation - Heru Satria Tambunan; Indra Gunawan; Sumarno Sumarno (STMIK Budi Darma, 2019)
STIKOM Tunas Bangsa is a world education institution located in the area of North Sumatra, where every semester for students who get PPA and BBP scholarships, from the number of students who come from it, not all students get scholarships, and at least get scholarships provided. Each student has the same criteria as the number of scholarships, with a minimum number of scholarship recipients. Therefore, to determine the number of participants who receive PPA scholarships in each country STIKOM Tunas Bangsa. In predicting the number of Kouta scholarship recipients using Backpropagation artificial nerves using data from 2015 to 2019 the data used from previous data has been received by the STIKOM Tunas Bangsa campus. With the existence of this artificial neural network to predict 2020 the number of PPA and BBP scholarship recipients at STIKOM Tunas Bangsa.